The incredible hulk how the legend began - Johnson, Kenneth, 1942-; Bixby, Bill, 1934-1993; Ferrigno, Lou; Hartley, Mariette; Universal Television (Firm); Marvel Comics Group; Universal Pictures (Firm) (Universal City, CA : Universal, 2003)
While conducting a research project about superhuman strength, Dr. Banner bombards his own system with gamma radiation, unexpectedly transforming himself into the powerful beast, "The Incredible Hulk."
Title from container.
Pilot episode of the CBS television series, originally broadcast in 1978.
Based on the characters created by Marvel Comics.
Bill Bixby, Lou Ferrigno, Mariette Hartley.
Not rated.
VHS.
Keywords: Incredible Hulk (Fictitious character) -- Drama; Science fiction television programs -- United States; Video recordings for the hearing impaired